Stylistic Features of Netspeak Language on 9GAG’s Instagram Account - I Gede Sumerta Yasa; Putu Nur Ayomi; Putu Devi Maharani (Journal of Language and Literature, 2023)
The emergence of Netspeak as a variety of languages cannot be separated from the development of the Internet and social media. The characteristic of its medium and the social media nature of communication makes Netspeak have distinctive and unique features that differentiate it from the more traditional form of communication, such as topographic and grammatical irregularities, as well as lexical creativity. This study attempts to discover the use of written communication features on 9GAG’s Instagram account as a popular community-based content creator. The qualitative method is applied by using Crystal’s feature of language variety model. The data was gathered through observation and documentation and then analyzed in terms of graphology, typography, grammar, vocabulary, and discourse features. This research found some distinctive graphic features such as punctuations and spellings, morphological processes and syntactical irregularities, distinctive vocabularies, and some discourse feature that presents unique coherence and chronological order. The finding indicates the rich features present in the data source, with the characteristics of informality and irregularities that often bend the rules of standard language imposed by internet users. Moreover, the finding also shows that the written language development on Netspeak is a way to overcome the barriers to expression in Instagram communication.